Enhanced Immunity and Infection Resistance in Mice Through Co-Expression of Porcine IL-3, IL-7, and IL-15 Fusion Molecules in Yarrowia lipolytica - Junjie Peng; Linhan Zhang; Jiangling Li; Xuebin Lv; Rui Liu; Jianlin Chen; Gang Wang; Rong Gao (Biology)
China’s livestock industry grapples with challenges posed by infectious diseases and the misuse of antibiotics, resulting in a heightened risk of drug-resistant pathogens. This study explored the immunomodulatory effects of co-expressing porcine interleukin 3, 7, and 15 in Yarrowia lipolytica, denoted as Po1h-IL-3/7/15. A 42-day experiment involving mouse immunization and pathogen challenge was conducted, during which in vivo assessments of antibodies, immune-related cells, and gene expression were detected following oral administration of Po1h-IL-3/7/15. Immunological alterations in mice were analyzed using flow cytometry, qRT-PCR, ELISA, and HE staining. Notably, the serum IgG and intestinal sIgA levels in the Po1h-IL-3/7/15 group were substantially elevated compared to the control groups (p < 0.01), so were the contents of IL-7, IL-15, IFN-γ, IL-22, IL-23, and TNF-α. Furthermore, there was a marked increase in naïve T cells and central memory T cells, accompanied by a significant decrease in regulatory T cells in peripheral blood. Post-challenge with Staphylococcus aureus or Salmonella typhimurium, the expression levels of BD2, IL-1β, IL-8, Jak1, RegⅢ, S100A8, STAT1, and TNF-α genes in the intestines of the Po1h-IL-3/7/15 group were markedly higher than those in the control groups (p < 0.01). Following the challenges, the survival rate of the Po1h-IL-3/7/15 group was 100%, a significant increase compared to the 20% and 40% survival rates observed in the control groups (p < 0.05). These results confirm that IL-3/7/15 significantly boosts innate immunity, humoral and cell-mediated immune responses, and intestinal mucosal immunity in mice, enhancing resistance to bacterial infections and exhibiting potent protective effects.